1997
DOI: 10.1099/0022-1317-78-5-1165
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and taxonomy of maize chlorotic dwarf virus within the family Sequiviridae.

Abstract: The complete sequence of a Tennessee isolate of maize chlorotic dwarf virus (MCDV-TN) was determined from cDNA clones and by direct sequencing of the viral RNA. The genome is 11 813 nucleotides (nt) in length and contains one large open reading frame between nt 435 and 10763 that encodes a polyprotein of 3443 amino acids. The Nterminal amino acid sequences were determined for the three capsid proteins. All three were adjacent,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…The predicted catalytic triads of PYFV sequivirus and rice tungro spherical waikavirus (RTSV) are formed by His, Glu, and Cys (Figs. In agreement with these data, N-terminal amino acid sequencing has revealed that the RTSV (Shen et al, 1993) and MCDV (Reddick et al, 1997) CPs probably arise from proteolytic cleavages at Gln-x dipeptide, whereas no consensus sequence can be found for the cleavage sites that originate the PYFV CPs (Ser-Pro, Asn-Ala, and Gln-Ala) (Turnbull-Ross et al, 1993). However, the proposed acidic active site residue of maize chlorotic dwarf waikavirus (MCDV) is an Asp residue (Reddick et al, 1997).…”
Section: Sequiviridaementioning
confidence: 68%
See 3 more Smart Citations
“…The predicted catalytic triads of PYFV sequivirus and rice tungro spherical waikavirus (RTSV) are formed by His, Glu, and Cys (Figs. In agreement with these data, N-terminal amino acid sequencing has revealed that the RTSV (Shen et al, 1993) and MCDV (Reddick et al, 1997) CPs probably arise from proteolytic cleavages at Gln-x dipeptide, whereas no consensus sequence can be found for the cleavage sites that originate the PYFV CPs (Ser-Pro, Asn-Ala, and Gln-Ala) (Turnbull-Ross et al, 1993). However, the proposed acidic active site residue of maize chlorotic dwarf waikavirus (MCDV) is an Asp residue (Reddick et al, 1997).…”
Section: Sequiviridaementioning
confidence: 68%
“…The monopartite genome of sequi-and waikaviruses differs from that of the potyviruses in encoding three capsid proteins (like animal picornaviruses), located internally near the N-terminus of the large polyprotein (Fig. Particular features of the waikaviruses are long AUG-containing sequences upstream of the large genomic ORF and small 3 ~ ORFs that might be expressed by subgenomic RNAs (Shen et al, 1993;Reddick et al, 1997). Particular features of the waikaviruses are long AUG-containing sequences upstream of the large genomic ORF and small 3 ~ ORFs that might be expressed by subgenomic RNAs (Shen et al, 1993;Reddick et al, 1997).…”
Section: Sequiviridaementioning
confidence: 99%
See 2 more Smart Citations
“…3). Particular features of the waikaviruses are long AUG-containing sequences upstream of the large genomic ORF and small 3 ~ ORFs that might be expressed by subgenomic RNAs (Shen et al, 1993;Reddick et al, 1997). The genomic RNA of parsnip yellow fleck sequivirus (PYFV) lacks a poly-A tail (Turnbull-Ross et al, 1992).…”
Section: Sequiviridaementioning
confidence: 99%